Studies of Ciprofloxacin Encapsulation on Alginate/Pectin Matrixes and Its Relationship with Biodisponibility - Islan, Germán Abel (2012)
Screening of ciprofloxacin (Cip) with selected biopolymers brings about 90% antibiotic interactions with a coacervate composed of alginate/high metoxylated pectin in 2:1 ratio. Fourier transform infrared spectroscopy analysis provides information about the nature of this interaction, revealing ionic and hydrophobic patterns among the molecules. Alginate/high methoxylated pectin gel microspheres developed by ionic gelation encapsulates 46.8 ± 5.0% Cip. The gel matrix can release Cip in a sustained manner, releasing 42.7 ± 0.2% in 2 h under simulated stomach pH conditions, and 83.3 ± 1.1% Cip release in 80 mM phosphate at pH = 7.40 (intestinal). The increase of sodium chloride from 50 to 200 mM implies a Cip release from 69.0 ± 1.5% to 95.1 ± 3.6% respectively in 2 h. Scanning electron microscopy revealed the cohesive effect of HM pectin over alginate molecules on the microsphere surface. Those results guarantee all Cip contained in the alginate/HM pectin microspheres could be released in an established kinetic profile along the gastrointestinal tract, avoiding the Cip undesirable side effects during absorption.